2020
DOI: 10.1007/s00246-020-02355-6
|View full text |Cite
|
Sign up to set email alerts
|

Left and Right Ventricular Impairment Shortly After Correction of Tetralogy of Fallot

Abstract: Surgical repair of Tetralogy of Fallot (ToF) is usually performed in the first months of life with low early postoperative mortality. During long-term follow-up, however, both right (RV) and left ventricular (LV) performances may deteriorate. Tissue Doppler imaging (TDI) and speckle tracking echocardiography (ST) can unmask a diminished RV and LV performance. The objective of the current study was to assess the cardiac performance before and shortly after corrective surgery in ToF patients using conventional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…These findings are in agreement with previous studies describing temporarily decreased ventricular performance following ToF repair. 21 22 Biventricular GLS following PVR did not differ statistically significantly across study time points. TDI TV S′—another parameter of RV function—did follow a pattern of temporarily impaired ventricular function.…”
Section: Discussionmentioning
confidence: 79%
“…These findings are in agreement with previous studies describing temporarily decreased ventricular performance following ToF repair. 21 22 Biventricular GLS following PVR did not differ statistically significantly across study time points. TDI TV S′—another parameter of RV function—did follow a pattern of temporarily impaired ventricular function.…”
Section: Discussionmentioning
confidence: 79%
“…Weidemann et al report has shown abnormal function in regional biventricular systolic myocardial function in asymptomatic repaired TOF children that are related to irregular electrical depolarization in the right ventricle 23 . Furthermore, a recent study in the assessment of biventricular function utilizing tissue Doppler imaging and speckle tracking has shown a significant decrease in left interventricular septum strain shortly after TOF surgery, but not in the fractional shortening 21 . Although ventricular strain worsens early after surgical repair, DiLorenzo et al have demonstrated that strain recovers through two postoperative years but long‐term ventricular dysfunction may begin early after surgery 24 …”
Section: Discussionmentioning
confidence: 97%
“…This utilizing tissue Doppler imaging and speckle tracking has shown a significant decrease in left interventricular septum strain shortly after TOF surgery, but not in the fractional shortening. 21 Although ventricular strain worsens early after surgical repair, DiLorenzo et al have demonstrated that strain recovers through two postoperative years but long-term ventricular dysfunction may begin early after surgery. 24 Our findings revealed a significant correlation between left ventricular strain and aortic cross-lamp time and cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown varying degrees of histopathological changes and mild fibrosis in muscle specimens from TOF patients ( 11 , 18 ). Some studies found the function of both the left and right ventricles to be damaged ( 19 ), which is also believed to be related to myocardial fibrosis ( 20 ). Notably, TP repair can lead to pulmonary regurgitation (PR), inducing RV volume overload and often progressive RV dilation, which may include the development of tricuspid regurgitation and RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%